2023
DOI: 10.1029/2022jd037471
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between African Easterly Waves and Tropical Cyclones in Historical and Future Climates in the HighResMIP‐PRIMAVERA Simulations

Abstract: Tropical cyclones (TCs) and their associated heavy precipitation, high winds, and storm surges are both deadly and destructive, leading to losses in the United States that can often exceed $1 billion for an individual event (Cerveny et al., 2017;NOAA, 2021;Yue et al., 2012). The genesis of these extreme events hinges on the co-occurrence of multiple environmental factors, including warm sea surface temperatures (SSTs), a moist mid-troposphere, weak vertical wind shear, and an initial precursor or "seed" distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Previous research has clearly shown a consensus that developing AEWs tend to be stronger than non‐developing AEWs (Agudelo et al., 2011; Bercos‐Hickey et al., 2023; Enyew & Mekonnen, 2022; Hopsch et al., 2009). Indeed, Atlantic hurricane season reports often cite vigorous AEWs as the initial disturbances of Atlantic TCs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has clearly shown a consensus that developing AEWs tend to be stronger than non‐developing AEWs (Agudelo et al., 2011; Bercos‐Hickey et al., 2023; Enyew & Mekonnen, 2022; Hopsch et al., 2009). Indeed, Atlantic hurricane season reports often cite vigorous AEWs as the initial disturbances of Atlantic TCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, out of a 23‐year average of 58 tropical waves that moved across the Atlantic during hurricane season, only 30% developed into TCs (Avila, 1991). Many studies have therefore examined the characteristics and environments of developing and non‐developing waves in an effort to understand the circumstances under which AEWs lead to tropical cyclogenesis (Asaadi et al., 2016, 2017; Bercos‐Hickey et al., 2023; Dunkerton et al., 2009; Enyew & Mekonnen, 2022; Hopsch et al., 2009; Núñez Ocasio et al., 2021; Peng et al., 2012; Ross et al., 2009; Z. Wang et al., 2012). Dunkerton et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A seed disturbance is a convective weak vortex that is generated within the large‐scale circulation (Hsieh et al., 2022), which can then evolve into a TC depending on the environmental conditions (Hoogewind et al., 2020; Hsieh et al., 2020; Tang & Camargo, 2014; Vecchi et al., 2019; Yang et al., 2021). Many previous studies have examined how convection drives AEWs and how AEWs serve as seed disturbances for TCs (Avila & Pasch, 1992; Bercos‐Hickey et al., 2023; Berry & Thorncroft, 2012; Chen & Dudhia, 2001; N. L. Frank, 1970; Hopsch et al., 2007, 2009; Landsea, 1993; Núñez Ocasio & Rios‐Berrios, 2023; Russell & Aiyyer, 2020; Thorncroft & Hodges, 2001). For example, Thorncroft and Hodges (2001) found that tracked AEWs in reanalysis data were positively correlated with Atlantic TC activity between 1985 and 1998 and that TC activity was mostly associated with the south AEW track.…”
Section: Introductionmentioning
confidence: 99%